(untitled) (Research, Society and Development, 2024)
This study aimed to review and synthesize the most recent evidence on diagnostic approaches for Hirschsprung’s disease, a congenital condition characterized by the absence of ganglion cells in the intestine, resulting in functional obstruction. The research focused on advances in clinical, histopathological, imaging, and genetic methods, emphasizing their implications for medical practice and therapeutic management. The literature review was conducted in databases such as PubMed, SciELO, and BIREME, considering studies published between 2013 and 2023, in English, Portuguese, and Spanish. Rectal biopsy remains the diagnostic gold standard, offering high specificity in identifying aganglionosis. Imaging methods, such as contrast-enhanced radiographs, are useful in initial screening but have limitations in atypical cases. Anorectal manometry demonstrates its efficacy in detecting the absent inhibitory reflex and is widely used in specialized centers. Recently, genetic tests, especially those involving mutations in the RET gene, have been explored as complementary tools, contributing to early diagnosis and identification of hereditary variants. It is concluded that the diagnostic approach to Hirschsprung’s disease has evolved significantly with the incorporation of advanced techniques. Despite this, gaps remain, such as the need for standardized protocols integrating traditional and modern methods for greater diagnostic accuracy. Future studies should explore the clinical feasibility of new technologies and their impact on patient outcomes. Thus, this review contributes to a comprehensive and updated understanding, promoting advances in medical practice.